Electronic music effects on neuromuscular and cardiovascular systems and psychophysiological parameters during exhaustive incremental test - B.P.C. Smirmaul; J.L. Dantas; E.B. Fontes; A.C. Moraes (Desafio Singular, 2011)
The aim of this study was to analyze the music effects on physiological and psychophysiological responses, as well as on the maximum power output attained during an incremental test. A sample of 10 healthy individuals (20.8 ± 1.4 years, 77.0 ± 12.0 kg, 179.2 ± 6.3 cm) participated in this study. It was recorded the electromyographic activity (muscles Rectus Femoris − RF and Vastus Lateralis − VL), heart rate (HR), rating of perceived exertion (RPE), ratings of perceived time (RPT) and the maximum power output attained (PMax) during music (WM) and without music (WTM) conditions. The individuals completed four maximal incremental tests (MIT) ramp-like on a cycle simulator with initial load of 100 W and increments of 10 W•min-1. The mean values of PMax between conditions WTM (260.5 ± 27.7 W) and WM (263.2 ± 17.2 W) were not statistically different. The comparison between the rates of increase of the values expressed in root-mean-square (RMS) and median frequency (MF) for both muscles (RF and VL) also showed no statistical difference, as well as HR, RPE and RPT. It is concluded that the use of the electronic music during an incremental test to exhaustion showed no effect on the analyzed variables for the investigated group.